A Survey on Information Need and Information Seeking Behavior of Library Users of NRN Memorial National Law Library - Yaranal, Mahesh A.; Ramesha (Journal of Information and Knowledge, 2016)
The present paper is based on a survey conducted on the information needs and information seeking behavior of library users of NRN Memorial National Law Library, National Law School of India University, Bangalore. The survey was conducted recently and the paper points out the changing information needs of the users. The usefulness of collection and services of the library and also examined the various types of collections and services are being used by the individual users of the national library. Identified the various infrastructure facilities are being provided by the library. Finally measures to be taken to make library services more effective and efficient.